Sleep Quality and Work Shifts: A Study of Industrial Workers in an Industrial Area of Assam, India - Mousumi Krishnatreya; Rinku Borah (Research Highlights in Disease and Health Research Vol. 8, 2023)
This book chapter discusses the prevalence of sleep disorders among shift workers and day workers in the industrialized societies of India, with a focus on the North Eastern region of the country. The symptoms of sleep disorders vary depending on the amount and quality of sleep obtained by individuals engaged in different types of shift work. The study aims to compare the prevalence of sleep disorders in both groups based on International Classification of Sleep Disorders (ICSD) criteria. Data was collected from 161 shift workers and 161 permanent day workers from 16 industries in North Guwahati, Assam, from July to December 2021 using a well-validated questionnaire. The results indicate a higher prevalence of general sleep disturbance among shift workers (34%) compared to day workers (19%), and a higher prevalence of Insomnia and Restless leg syndrome in shift workers. The variability of their sleep times is associated with these ICSD-defined symptoms of sleep disorders like Insomnia, Obstructive sleep apnea and Restless leg syndrome. The study emphasizes the necessity for occupational health interventions focused at lowering sleep issues and enhancing shift workers’ resilience, especially in regions with new industrial expansion. This book chapter adds to the growing body of research on the impact of shift work on sleep quality in industrialized societies of India. It highlights the need for more research in the North Eastern region and emphasizes the importance of addressing the sleep problems of shift workers in occupational health interventions.